The effect of interleukin-17 on the course of juvenile idiopathic arthritis - Oshlyanska, O.; I.V. Dzyublyk; N.A. Melanchuk + https://orcid.org/0000-0003-4320-8250 (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Juvenile idiopathic arthritis (JIA) is a heterogeneous group of chronic joint diseases in children who have different course and prognosis, so they continue to be investigated. In the presented part of the study, the content of soluble ІL-17-retseptoru, ІL-1 and γ -interferon in blood serum was determined to assess the role of their ratios and cooperation in the course of the disease in various subvariants of JIA. This will make it possible to predict the further course of the disease and choose the right treatment tactics.